Association between the severity of constipation and sarcopenia in elderly adults: A single‑center university hospital‑based, cross‑sectional study. Issue 1 (22nd September 2020) - ASAOKA, DAISUKE; TAKEDA, TSUTOMU; INAMI, YOSHIHIRO; ABE, DAIKI; SHIMADA, YUJI; MATSUMOTO, KENSHI; UEYAMA, HIROYA; MATSUMOTO, KOHEI; KOMORI, HIROYUKI; AKAZAWA, YOICHI; OSADA, TARO; HOJO, MARIKO; et al.
No abstract available